2000
DOI: 10.1016/s0028-3932(00)00038-5
|View full text |Cite
|
Sign up to set email alerts
|

Language and calculation within the parietal lobe: a combined cognitive, anatomical and fMRI study

Abstract: We report the case of a patient (ATH) who suered from aphasia, deep dyslexia, and acalculia, following a lesion in her left perisylvian area. She showed a severe impairment in all tasks involving numbers in a verbal format, such as reading aloud, writing to dictation, or responding verbally to questions of numerical knowledge. In contrast, her ability to manipulate nonverbal representations of numbers, i.e., Arabic numerals and quantities, was comparatively well preserved, as evidenced for instance in number c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 38 publications
7
128
1
4
Order By: Relevance
“…This hypothesis has been supported by several neuropsychological studies. Researchers have found that patients with lesions in the left perisylvian language region and those with low verbal fluency had more difficulty in single-digit multiplication than in addition and subtraction (e.g., Cohen, Dehaene, Chochon, Lehéricy, & Naccache, 2000;Dehaene & Cohen, 1997;Delazer & Benke, 1997;Lemer, Dehaene, Spelke, & Cohen, 2003;Pesenti, Seron, & van der Linden, 1994;van Harskamp, Rudge, & Cipolotti, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been supported by several neuropsychological studies. Researchers have found that patients with lesions in the left perisylvian language region and those with low verbal fluency had more difficulty in single-digit multiplication than in addition and subtraction (e.g., Cohen, Dehaene, Chochon, Lehéricy, & Naccache, 2000;Dehaene & Cohen, 1997;Delazer & Benke, 1997;Lemer, Dehaene, Spelke, & Cohen, 2003;Pesenti, Seron, & van der Linden, 1994;van Harskamp, Rudge, & Cipolotti, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…however, broad cortical injuries that also involve regions proximal to the left temporal cortex, left and right parietal and frontal lobe, are susceptible to conduct concomitant language disorders and numerical and calculating processing [13][14][15][16] .…”
mentioning
confidence: 99%
“…Authors reported that first-order and higher-order quantifiers both recruit right inferior parietal cortex, suggesting that a numerosity component contributes to quantifier comprehension. In fact, parietal activation was also widely reported in subjects asked to perform a simple number processing tasks [20,21,22,23,24] or arithmetic tasks [ 11,25,26].…”
Section: Discussionmentioning
confidence: 87%